1996
DOI: 10.1016/0014-5793(96)00064-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of glycated aminophospholipids from red cells and plasma of diabetic blood

Abstract: Glycosylation is a major pathway for posttranslational modification of tissue protein and begins with nonenzymatic addition of carbohydrate to the primary amino groups. Excessive glycation of tissue protein has been implicated in the pathogenesis of diabetes and ageing. While glycation of aminophospholipids has also been postulated, glycated aminophospholipids have not been isolated. Using normal phase HPLC with on-line electrospray mass spectrometry we found glycated ethanolamine phospholipids to make up 10-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 21 publications
5
75
0
Order By: Relevance
“…However, in this study, glycated PS was undetectable in human plasma (data not shown). Similarly, Ravandi et al (25) were also unable to detect glycated PS in human plasma or red blood cell membranes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, in this study, glycated PS was undetectable in human plasma (data not shown). Similarly, Ravandi et al (25) were also unable to detect glycated PS in human plasma or red blood cell membranes.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies reported the detection of Amadori-PE in biological samples (i.e., blood plasma, red blood cells, and human atherosclerotic plaques) using LC-MS (25)(26)(27)(28). During LC-MS analysis, chromatographic peaks that showed mass increments of 162 Da (most likely C 6 H 10 O 5 ) relative to the molecular masses of nonglycated PE were tentatively ascribed to Amadori-PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that the amino phospholipids of plasma and red blood cells (RBC) from diabetic subjects show a 10-fold increase in glycated PtdEtn over control subjects (9,10) and that incorporation of Glc-PtdEtn into LDL (11) facilitates peroxidation of LDL lipids. The present study demonstrates that the presence of Glc-PtdEtn in LDL results in an increased uptake of LDL and a dramatic increase in neutral lipid accumulation in THP-1 macrophages.…”
Section: Ldlmentioning
confidence: 99%